ChemInform Abstract: A Two‐Step Synthesis of Selected 1, 2, 3, 4‐Tetrahydroquinoxaline Derivatives from N‐Aryl‐2‐nitrosoanilines and Arylidenecyanoacetic Esters. Issue 7 (18th February 2014) - Krolikiewicz, Magdalena; Blaziak, Kacper; Danikiewicz, Witold; Wrobel, Zbigniew
Abstract Sequential nucleophilic addition of nitroaniline to alkyl arylidenecyanoacetates and intramolecular cyclization provides tetrahydroquinoxaline derivatives with excellent regio‐ and diastereoselectivity.